Mild Cognitive Impairment and Donepezil Impact Mitochondrial Respiratory Capacity in Skeletal Muscle. Issue 6 (2nd September 2021) - Morris, Jill K; McCoin, Colin S; Fuller, Kelly N; John, Casey S; Wilkins, Heather M; Green, Zachary D; Wang, Xiaowan; Sharma, Palash; Burns, Jeffrey M; Vidoni, Eric D; Mahnken, Jonathan D; Shankar, Kartik; et al.
Abstract: Alzheimer's Disease (ad ) associates with insulin resistance and low aerobic capacity, suggestive of impaired skeletal muscle mitochondrial function. However, this has not been directly measured in AD. This study ( n = 50) compared muscle mitochondrial respiratory function and gene expression profiling in cognitively healthy older adults (CH; n = 24) to 26 individuals in the earliest phase of ad -related cognitive decline, mild cognitive impairment (MCI; n = 11) or MCI taking the ad medication donepezil (MCI + med; n = 15). Mitochondrial respiratory kinetics were measured in permeabilized muscle fibers from muscle biopsies of the vastus lateralis. Untreated MCI exhibited lower lipid-stimulated skeletal muscle mitochondrial respiration (State 3, ADP-stimulated) than both CH ( P = .043) and MCI + med ( P = .007) groups. MCI also exhibited poorer mitochondrial coupling control compared to CH ( P = .014). RNA sequencing of skeletal muscle revealed unique differences in mitochondrial function and metabolism genes based on both MCI status (CH vs MCI) and medication treatment (MCI vs MCI + med). MCI + med modified over 600 skeletal muscle genes compared to MCI suggesting donepezil powerfully impacts the transcriptional profile of muscle. Overall, skeletal muscle mitochondrial respiration is altered in untreated MCI but normalized in donepezil-treated MCI participants while leak control is impaired regardless of medication status. These results provide evidence that mitochondrial changes occur in the early stages of AD, but are influenced by a common ad medicine. Further study of mitochondrial bioenergetics and the influence of transcriptional regulation in early ad is warranted. Graphical Abstract: